Impact of Gratitude on Mental Health of Adults: Mediating Role of Prosocial Behavior - Islam, Zain ul; Khan, Maria Anwar; Farooq, Aiman; Aslam, Saira (Pakistan Journal of Applied Psychology (PJAP), 2022)
The present study aimed to examine the mediating influence of prosocial behavior between gratitude and mental health among adults. Sample size was justified from A-priori sample size calculator for structural equation modeling (Soper, 2021). The sample comprised of 420 adults who were purposefully selected with an age range of 18-26 years. Data were collected from major cities of Punjab (Lahore, Multan and Faisalabad) through online google form survey. Three questionnaires were employed; The Gratitude Questionnaire-GQ-6 (McCullough, 2013), depression and anxiety subscales from Mental Health Inventory-MHI-18 (Veit & Ware, 1983) and Prosocial Tendencies Measures-PTM (Carlo & Randal, 2002). After collecting the data for desired sample size, results were analyzed through SPSS (24.0), which revealed that there was a significant correlation between gratitude, prosocial behavior, and mental health among adults. Moreover, the results also found that there is a significant impact of gratitude on mental health through mediation of prosocial behavior among adults. This study will be helpful for adults, students, and consultants to recognize the precipitating and perpetuating factors to improve their mental health.